2007
DOI: 10.1002/chin.200729039
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrazole and Isoxazole in Triethanolamine Medium.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Chalcones dibromides, obtained from the treatment of chalcones with bromine, afforded pyrazoles by the reaction with benzoylhydrazines [186] and phenylhydrazines [115] in dry pyridine or hydrazines in triethanolamine [187], and 2-pyrazolines by the reaction with phenylhydrazine or isonicotinic acid hydrazide in DMF (Scheme 20) [188]. A series of bispyrazoles can be accomplished through the reaction of bischalcones tetrabromo derivatives with hydrazine hydrate in refluxing methanol [189].…”
Section: Transformation Of Chalcones To Pyrazolesmentioning
confidence: 99%
“…Chalcones dibromides, obtained from the treatment of chalcones with bromine, afforded pyrazoles by the reaction with benzoylhydrazines [186] and phenylhydrazines [115] in dry pyridine or hydrazines in triethanolamine [187], and 2-pyrazolines by the reaction with phenylhydrazine or isonicotinic acid hydrazide in DMF (Scheme 20) [188]. A series of bispyrazoles can be accomplished through the reaction of bischalcones tetrabromo derivatives with hydrazine hydrate in refluxing methanol [189].…”
Section: Transformation Of Chalcones To Pyrazolesmentioning
confidence: 99%
“…The chalcones are precursors in the biosynthetic pathways of flavonoids, isoflavonoids, and aurone, which reportedly have wide-ranging pharmacological activities, such as antifungal (Zhao et al, 2007), antibacterial (Nielsen et al, 2005), antioxidant (Aichaoui et al, 2009), anticancer (Mahmoodi et al, 2014), antiprotozoal (Kiat et al, 2006), antiinflammatory (Seo et al, 2005), antimalarial (Awasthi et al, 2009), anti-HIV (Cheenpracha et al, 2006), anti-angiogenic (Varinska et al, 2012), cyclooxygenase inhibitory (Sharma, 2014) and tyrosine phosphatase 1B inhibitory activities (Sun et al, 2012). Chalcones and their α,β-dibromo derivatives (2,3-dibromo-1,3-diphenyl-2-propen-1-one) are used as intermediates for the syntheses of various heterocyclic compounds, such as flavones, flavonols, aziridines, coumarones, quinolines, pyrazoles and isooxazoles (Tökés et al, 1992;Wróblewski et al, 2000;Agrawal & Soni, 2007). A survey of the literature revealed that α,β-dibromochalcones and their derivatives also possess a wide range of biological activities, which include antioxidant (Lahsasni et al, 2014), antimicrobial (Rahman et al, 2012), anti-angiogenic (Robinson et al, 2005), quinine reductase-inducing (Dinkova-Kostova et al, 1998), cytotoxic (Modzelewska et al, 2006) and cholesterol-lowering activities (Piantadosi et al, 1973).…”
Section: Introductionmentioning
confidence: 99%